Effect of Chromium on Growth of green ALGA SCENEDESMUS QUADR ICAUDA (TURP.) DE BERB. With increase of nitrogen concentration (Baghdad Science Journal, 2010)
The study was conducted to identify the toxicity of chromium on scenedesmus quadricauda algae alone and in the presence of nutrient metal (Nitrogen). Different concentrations of chromium (0.5, 1.5 , 2.5, 3.5 , 4.5mg/L) were used and the presence nitrogen is (5 ,10 ,50 ,100mg/L) on cultur media(chu-10) with used for cultivation of the algae in controlled conditions(25oC , light intensity 380 –?E/m2 /s. The results showed increasing in the toxicity of the metal when is alone , excess of concentrations an time of exposure. The growth rate decreased from 0.44 to 0.06 cell/ hour after 12 day of the biging of the experiment and of concentrate 4.5 mg/L of chromium. The intermediate active concentrations of the chromium(EC50) was increased after 96 hours from the exposure, which it reached alevel at 3mg/L, which the increase of rate of inhibition which became 64, 80, 87 and 90% respectively with above mentioned concentrations of chromium. While after increasing the nitrogen concentrations in the culture media , an decrease was detected in the toxicity of the chromium at 3mg/L . Level through the increase in growth rate reached 0.30 cell /hour after the addition of 5mg/L of Nitrogen to the culture media which contain 3mg/L of chromium. This increase was also a companied by a decrease in rate of inhibition at a level of 74%, 69%, 78%, 70% respectively with the above mentioned treatment concentrations. From the above results it could be concluded that the toxicity of chromium may be declined under the effect of the Nitrogen